Full Transcriptome Analysis of Callus Suspension Culture System of Bletilla striata - Li, Lin; Liu, Houbo; Wen, Weie; Huang, Ceyin; Li, Xiaomei; Xiao, Shiji; Wu, Mingkai; Shi, Junhua; Xu, Delin (Frontiers in Genetics, 2020)
Background: Bletilla striata has been widely used in pharmacology industry. To effectively produce the secondary metabolites through suspension cultured cells of B. striata, it is key important to exploring the full-length transcriptome data and the genes related to cell growth and chemical producing of all culture stages. We applied a combination of Real-Time Sequencing of Single Molecule (SMRT) and second-generation sequencing (SGS) to generate the complete and full-length transcriptome of B. striata suspension cultured cells. Methods: The B. striata transcriptome was formed in de novo way by using PacBio isoform sequencing (Iso-Seq) on a pooled RNA sample derived from 23 samples of 10 culture stages, to explore the potential for capturing full-length transcript isoforms. All unigenes were obtained after splicing, assembling, and clustering, and corrected by the SGS results. The obtained unigenes were compared with the database, and the functions were annotated and classified. Results and conclusions: A total of 100,276 high-quality full-length transcripts were obtained, with an average length of 2530 bp and an N50 of 3302 bp. About 52% of total sequences were annotated against the Gene Ontology, 53,316 unigenes were hit by KOG annotations and divided into 26 functional categories, 80,020 unigenes were mapped by KEGG annotations and clustered into 363 pathways. Furthermore, 15,133 long-chain noncoding RNAs (lncRNAs) were detected and 68,996 coding sequences were identified based on SSR analysis. In conclusion, our results provide new full-length transcriptome data and genetic resources for identifying growth and metabolism-related genes, which provide a solid foundation for further research on its growth regulation mechanisms and genetic engineering breeding mechanisms of B. striata.